A Conceptual Overview of Enterprise Resource Planning Systems - Muhammad Yasir, Khan; Rossazana, Ab. Rahim; Yeng, Sin Kit (Human Resource Management Academic Research Society (HRMARS), 2025)
As digital transformation reshapes modern enterprises, Enterprise Resource Planning (ERP) systems have become essential tools for integrating and optimizing core business processes. This conceptual paper provides a comprehensive overview of ERP systems by synthesizing recent academic literature on their evolution, definitions, technical architecture, key characteristics, and modular structure. Emphasizing ERP's role as both a technological platform and a strategic enabler, the study highlights how ERP systems facilitate organizational efficiency, cross-functional coordination, and data-driven decision-making. The paper also explores emerging themes such as system flexibility, modularity, and integration in light of technological advancements. By offering a structured synthesis, this research serves as a foundational reference for scholars and practitioners seeking to understand ERP systems in the context of enterprise-wide digital innovation.